STRATEGI PENERAPAN MODEL PEMBELAJARAN INTERAKTIF BERBASIS MEDIA PADA PEMBELAJARAN MATEMATIKA KELAS V SD KOTA BAUBAU - Bela Man’Nuri Gaiful; Marna Marna; Nur Aina; Mustar Mustar; Suci Rahma Wati; Annisa Annisa; Siti Rahmalia Natsir (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of students’ interest and engagement in mathematics learning in elementary schools, which is still dominated by conventional teaching methods. This condition causes students to be passive, less motivated, and experience difficulties in understanding abstract mathematical concepts. This study aims to describe the strategy for implementing an interactive learning model based on media in mathematics learning for fifth-grade students in Baubau City. This study employed a qualitative approach with a descriptive type. The research subjects consisted of teachers and fifth-grade students of SD Negeri 1 Kaobula, selected using purposive sampling. Data collection techniques included observation, interviews, and documentation, while data validity was tested through source and technique triangulation. Data analysis used the Miles and Huberman model, which includes data collection, data reduction, data presentation, and conclusion drawing.The results of the study indicate that the strategy used by the teacher in implementing the interactive media-based learning model was carried out through three stages: planning, implementation, and evaluation. In the planning stage, the teacher prepared lesson plans, teaching materials, and interactive learning media such as PowerPoint presentations, instructional videos, and visual images tailored to the material. In the implementation stage, the teacher began the lesson by providing motivation and linking the material to students’ daily experiences, followed by the use of visual media and videos to attract students’ attention. Furthermore, the teacher applied interactive learning strategies by actively involving students in observing, questioning, group discussions, and problem-solving activities, while the teacher acted as a facilitator. In the evaluation stage, the teacher administered practice questions and conducted question-and-answer sessions to assess students’ understanding.The use of media such as PowerPoint, videos, and visual images was proven to help students understand abstract mathematical concepts more concretely and to increase students’ activeness in the learning process.